Attitudes of nursing students towards ageism and associated factors. - Capitó de Santana, Jaedson; Menezes de Peixoto Filho, Julio César; da Silva Araújo, Rose Dayanne; Silva Fhon, Jack Roberto; Maria de Lima, Fábia (Investigación & Educación en Enfermería)
Objective. To evaluate the associated factors on ageism in nursing students from a public university in Recife-PE. Methods. This is a cross-sectional, quantitative, analytical study, whose participants (n=215) were students of the bachelor’s degree in Nursing at a public university in Recife, Pernambuco, Brazil. Data regarding responses to a sociodemographic questionnaire and Fraboni Ageism Scale were analyzed. Results. The characteristics that predominated among the participants were: female (83.3%), age between 17-20 years (41.9%), single (92.1%), did not have a scholarship (83.5%), lived with parents and/or siblings (60.9%), had no child (98.1%), did not live with the older adult (74.4%), and was attending the first year of under graduation (28.4%). On the Fraboni Scale, the score was 36.74 out of 84 possible points for ageism, being by domain: 11.55 points for Avoidance, 11.54 points for Antilocution, and 10.05 points for Discrimination. Conclusion. Among the nursing students surveyed, ageism was associated with the male gender, younger age, not being a scholarship holder and living alone. Education and training aimed at caring for the older adults are effective tools to challenge prejudice related to aging.